The relative area of vessels in xylem correlates with stem embolism resistance within and between genera. (7th September 2022) - Avila, Rodrigo T; Kane, Cade N; Batz, Timothy A; Trabi, Christophe; Damatta, Fábio M; Jansen, Steven; McAdam, Scott A M
Abstract: The resistance of xylem conduits to embolism is a major factor defining drought tolerance and can set the distributional limits of species across rainfall gradients. Recent work suggests that the proximity of vessels to neighbors increases the vulnerability of a conduit. We therefore investigated whether the relative vessel area of xylem correlates with intra- and inter-generic variation in xylem embolism resistance in species pairs or triplets from the genera Acer, Cinnamomum, Ilex, Quercus and Persea, adapted to environments differing in aridity. We used the optical vulnerability method to assess embolism resistance in stems and conducted anatomical measurements on the xylem in which embolism resistance was quantified. Vessel lumen fraction (VLF) correlated with xylem embolism resistance across and within genera. A low VLF likely increases the resistance to gas movement between conduits, by diffusion or advection, whereas a high VLF enhances gas transport thorough increased conduit-to-conduit connectivity and reduced distances between conduits and therefore the likelihood of embolism propagation. We suggest that the rate of gas movement due to local pressure differences and xylem network connectivity is a central driver of embolism propagation in angiosperm vessels.